The Housing Market and Regional Commuting and Migration Choices. - Cameron, G; Muellbauer, J (CEPR, 1998)
Inter-regional migration is influenced by relative employment and earnings opportunities. But strongly offsetting forces operate from relative house prices. Commuting, at least to contiguous regions, is often an alternative to migration. Relative employment and earnings opportunities should influence commuting rates in the same direction as migration rates. Given the commute/migrate trade-off, however, housing market forces should operate in the opposite direction, particularly for contiguous regions. This paper presents evidence on inter-regional commuting and migration in Great Britain which is broadly in accord with these expectations. Data for the 1980s and 1990s on net commuting are derived from the ratios of numbers of employees resident in a region to the number employed in that region using Labour Force Survey and Census of Employment data. Information on migration comes from the National Health Service Central Register. Given the evidence for the importance of portfolio demand and speculative volatility in the British housing market presented in Muellbauer and Murphy (1997), this paper documents the important transmission effects via regional labour markets, for example, increasing regional mismatch, of the forces that drive house prices in Britain. The paper suggests tax reforms which should ameliorate these problems.